Marine Carotenoids - Sugawara, Tatsuya; Maoka, Takashi; Hosokawa, Masashi (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Carotenoids represent a large group of isoprenoid structures with many different structural characteristics and biological activities. They are the most important of the naturally occurring pigments and are responsible for the various colors of different fruits, vegetables, and plant parts. Marine carotenoids and their unique structures are responsible for the color of many fish, shellfish, and algae. However, while there have been many papers and reviews on carotenoids of terrestrial origin, there has been relatively little research conducted on the impact of marine carotenoids on human health. Recent research efforts have revealed that marine carotenoids have strong biological activity affecting human health and are candidates for nutraceuticals. This Topical Collection of Marine Drugs is dedicated to marine carotenoids, and will focus on the benefits of carotenoids for human beings. For a better understanding of the physiological effects of marine carotenoids, this collection should include the most recent developments in the presence, analysis, chemistry, and biochemistry of marine carotenoids.